Lao PDR Economic Monitor : November 2008 - World Bank (World Bank, Vientiane, 2013)
The Lao PDR economy continues to grow, but at a relatively slower pace as the impacts of the global financial turmoil are starting to be felt. Real gross domestic product (GDP) growth is expected to slow in 2008 to about 7 percent as result of the impacts of the global financial crisis. GDP growth is also projected to slow to between 5 and 6 percent in 2009. However, growth remains fairly strong and still driven by the ongoing hydropower projects as well as agro processing industries, construction and other services. The resource sector contributes over 2 percent and non-resource sectors another 5 percent to the growth rate in 2008. In addition to domestic consumption, medium-term growth will be sensitive to changes in global commodity prices (mainly metals and agriculture) as well as to demand and investment from neighboring countries (especially Thailand, China and Vietnam). It reports on recent economic performance (Part I), progress in the implementation of the Government's policy reform agenda (Part II), and donor activities in the relevant reform areas (Part III).